2017
DOI: 10.1101/157578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widely used commercial ELISA does not detect preHP-2, but recognizes properdin as a potential second member of the zonulin family

Abstract: Keywords: diabetes -lipid metabolism -pre-Haptoglobin 2 -ELISA -intestinal permeability 25 -properdin -obesity -metabolic diseases 26 27 Nonstandard abbreviations: HP, haptoglobin; T2D, type 2 diabetes; WHR, waist-to-hip 28 ratio.Abstract 30 BACKGROUND. There is increasing evidence for the role of impaired intestinal 31 permeability in obesity and associated metabolic diseases. Zonulin is an established serum 32 marker for intestinal permeability and identical to pre-haptoglobin2. Here, we aimed to 33 inve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
6
1
3
Order By: Relevance
“…Consequently, we are unable to make valid interpretations of our results with respect to our study cohorts (Fig 2). However, we found this assay to have a different capture antibody than the Immundiagnostik assay, which differs from conclusions made by Scheffler et al In both primary and follow-up publications, the authors list a table with studies that use the Immundiagnostik assay with a note that “the kit sold by other companies (e.g., ALPCO) is the same as the Immundiagnostik kit” [20, 21]. Our results do not agree with this claim, as there was poor strength of relationship between both commercial assays (Fig 3) and the immunoprecipitation protein products of both assays differed (Fig 4).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Consequently, we are unable to make valid interpretations of our results with respect to our study cohorts (Fig 2). However, we found this assay to have a different capture antibody than the Immundiagnostik assay, which differs from conclusions made by Scheffler et al In both primary and follow-up publications, the authors list a table with studies that use the Immundiagnostik assay with a note that “the kit sold by other companies (e.g., ALPCO) is the same as the Immundiagnostik kit” [20, 21]. Our results do not agree with this claim, as there was poor strength of relationship between both commercial assays (Fig 3) and the immunoprecipitation protein products of both assays differed (Fig 4).…”
Section: Discussioncontrasting
confidence: 89%
“…Dose-responses or signals to high concentrations were not observed; as such, the inability of recombinant zonulin to bind to captured antibodies was confirmed. In support of our ongoing observations, a publication was concurrently released which claimed that the Immundiagnostik assay was not detecting zonulin as advertised, but complement C3 instead [20]. Using an adapted protocol, the captured serum antigens as well as other components from both assays were immunoprecipitated then analysed by mass spectrometry.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ELISA is commonly used in laboratories to assess the integrity of the intestinal barrier. Scheffler [37] suggested that a serum zonulin (pre-HP2) test (Immundiagnostik ELISA kit) may simultaneously detect a variety of proteins that resemble zonulin structurally and perhaps functionally. This would mean the existence of a zonulin protein family instead of one protein structure regulating intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…30 In the current study, we used the Ussing chamber technology to assess barrier function, while the previous report relied on zonulin levels, for which the validity is currently questioned. 31,32 The increased variability seen in the FITC flux values may have contributed to the absence of statistical significance.…”
Section: Serum Bas Concentrations In Uc and CD Patientsmentioning
confidence: 99%